Schistosome-Associated Pulmonary Arterial Hypertension: A Review Emphasizing Pathogenesis - Ferrari, Teresa Cristina Abreu; Albricker, Ana Cristina Lopes; Gonçalves, Ina Morais; Freire, Cláudia Maria Vilas (Frontiers in Cardiovascular Medicine, 2021)
Schistosomiasis, especially due to Schistosoma mansoni, is a well-recognized cause of pulmonary arterial hypertension (PAH). The high prevalence of this helminthiasis makes schistosome-related PAH (Sch-PAH) one of the most common causes of this disorder worldwide. The pathogenic mechanisms underlying Sch-PAH remain largely unknown. Available evidence suggests that schistosome eggs reach the lung via portocaval shunts formed as a consequence of portal hypertension due to hepatosplenic schistosomiasis. Once deposited into the lungs, the eggs elicit an immune response resulting in periovular granuloma formation. Immune mediators drive transforming growth factor-β (TGF-β) release, which gives rise to pulmonary vascular inflammation with subsequent remodeling and development of angiomatoid and plexiform lesions. These mechanisms elicited by the eggs seem to become autonomous and the vascular lesions progress independently of the antigen. Portopulmonary hypertension, which pathogenesis is still uncertain, may also play a role in the genesis of Sch-PAH. Recently, there have been substantial advances in the diagnosis and treatment of PAH, but it remains a difficult condition to recognize and manage, and patients still die prematurely from right-heart failure. Echocardiography is used for screening, and the formal diagnosis requires right-heart catheterization. The experience in treating Sch-PAH is largely limited to the phosphodiesterase type 5 inhibitors, with evidence suggesting that these vasodilators improve symptoms and may also improve survival. Considering the great deal of uncertainty about Sch-PAH pathogenesis, course, and treatment, the aim of this review is to summarize current knowledge on this condition emphasizing its pathogenesis.